Implementation of GeoGebra-Assisted Problem Based Learning Model to Improve Understanding of Algebra Concepts in Junior High School - Syifaurrohman, Muhammad Huda; Shodikin, Ali (Journal of the Indonesian Mathematics Education Society, 2025)
This study investigates the effectiveness of the Problem Based Learning (PBL) model assisted by GeoGebra in improving junior high school students’ learning outcomes on the topic of the System of Linear Equations of Two Variables (SPLDV). The research is grounded in the existing problems in mathematics classrooms, where students often experience difficulties in understanding abstract concepts, exhibit low problem-solving abilities, and show limited interest in learning due to conventional, teacher-centered instructional approaches. GeoGebra, as an interactive digital tool, provides dynamic visualizations that help students connect algebraic theory with graphical representation, thereby facilitating deeper conceptual understanding. The findings reveal that the implementation of PBL assisted by GeoGebra significantly enhances students’ conceptual understanding, problem-solving skills, and learning interest. These results suggest that integrating technology-supported PBL can create more meaningful and engaging learning experiences. The study recommends that future research extend the application of this model to other mathematical topics and educational levels, as well as examine its long-term effects on affective aspects such as motivation and learning attitudes.